The Alternative to Post-Hegemony : Reproduction and Austerity’s Social Factory - Jarrett, Kylie (My University, 2014)
In the transitions to advanced liberal States and post-Fordist economic paradigms, it is argued that the distinction between work and sociality has become blurred. This marks the emergence of the “social factory” where sociality is industrialised and industrialisation has become increasingly centred on immaterial, social activity. It is further argued that this regime has generated a new articulation of socio-economic relations based on biopower and systems of control alongside the irruptive agency of multitude. Consequently, it is often suggested that the concept of hegemony can no longer adequately explain manifestations of power and resistance. The argument is that we live today in a state of post-hegemony. This paper challenges the theoretical and pragmatic underpinnings of this position at a number of levels, arguing that the lived politics associated with the imposition of Austerity economics across Europe, but particularly as manifest in Ireland, undermine the assertion that hegemony is no longer a relevant conceptualisation of power dynamics. In particular it uses feminist thinking to challenge the epochalisation inherent to arguments of post-hegemony, arguing instead for a return to engagement with the reproductive logic of hegemonic discipline.
Keywords: 306 Kultur und Institutionen; immaterial labour; hegemony; activism; feminism